P212 Characterisation of patients with expiratory large airway collapse. (12th November 2019) - Bikov, A; Bokhari, S; Niven, R; Allen, D; Somerton, C; Sheehan, R; Fowler, S
Abstract : Background: Tracheobronchomalacia (TBM) and excessive dynamic airway collapse (EDAC) are two forms of expiratory large airway collapse which is a potential, often underdiagnosed cause for unexplained cough, breathlessness, inability to expectorate and frequent infections. They can vary in aetiology, morphology, extent and severity. Proper characterisation of patients may help to identify different phenotypes, potentially contributing to more personalised treatment. Methods: We reviewed the database, bronchoscopy reports and video images of n=33 patients (27 female, age 54.5±12.9 years) who had been referred for treatment to a specialist respiratory physiotherapist for the diagnosis of expiratory large airway collapse. Patients were characterised according to the classification proposed by Murgu and Colt (Respirology, 2007). TBM and EDAC were scored in terms of extent (1=mild, <50% collapse, 2=focal, 3=multifocal, 4=diffuse), severity (1= <50% collapse, 2= 50–70% collapse, 3= 70–100%, 4= 100%), morphology (crescent, sabre-sheet, circumferential) and aetiology (idiopathic or secondary to lung disease). Results: Bronchoscopy had been performed in 32 subjects, and video available for review in 26 cases. Of these 26, the extent of collapse was mild in one, focal in nine, multifocal in seven, and diffuse in nine. The severity of collapse was <50% in one, 50–70% in seven, 70–100% in 15, and complete in three. There was a significant relationship between extent and severity (p=0.01, r=0.47). Two patients had circumferential collapse, the rest were crescent type. Associated diagnoses were: asthma in 23 patients; bronchiectasis in two; Ehlers-Danlos syndrome in one; and none of relevance in the six remaining. Conclusions: Expiratory large airway collapse is a multi-factorial disorder which can manifest in various extent and severity. Further observational studies are warranted to categorise patients and to see if these categories can predict treatment response.